Impact of Oseltamivir Treatment on Influenza A and B Virus Dynamics in Human Volunteers - Hooker, Kyla L.; Ganusov, Vitaly V. (Frontiers in Microbiology, 2021)
Influenza viruses infect millions of humans every year causing an estimated 400,000 deaths globally. Several antiviral drugs are available to treat influenza infection, and one of the most commonly used drugs is oseltamivir. While the mechanism of action of oseltamivir is well understood, the impact of oseltamivir on influenza virus dynamics in humans has been controversial. Many clinical trials with oseltamivir have been done by pharmaceutical companies but the results of these trials until recently have been reported as summary reports or papers. Typically, such reports included median virus shedding curves for placebo and drug-treated influenza virus infected volunteers often indicating high efficacy of the early treatment. Importantly, due to public pressure clinical trials data testing oseltamivir efficacy has been recently released in the form of redacted PDF documents. We digitized and re-analyzed experimental data on influenza virus shedding in human volunteers from three previously published trials: on influenza A or B viruses. We found that impact of oseltamivir on the virus shedding dynamics was dependent on i) selection of volunteers that were infected with the virus, and ii) the detection limit in the measurement assay; both of these details were not well articulated in the published studies. By assuming that any viral measurement is above the limit of detection we could match previously published data on median influenza A virus (flu A study) shedding but not on influenza B virus shedding (flu B study B) in human volunteers. Additional analyses confirmed that oseltamivir had an impact on the duration of shedding and overall shedding (defined as area under the curve) but this result was varied by the trial. Additional analyses showed that oseltamivir impacted the kinetics of the start and end of viral shedding and in about 20-40% of volunteers treatment had no impact on viral shedding duration. Our results suggest an unusual impact of oseltamivir on influenza viruses shedding kinetics and caution about the use of published median data or data from a few individuals for inferences. Furthermore, we call for the need to publish raw data from critical clinical trials that can be then independently analyzed.